2021
DOI: 10.1186/s41983-021-00329-w
|View full text |Cite
|
Sign up to set email alerts
|

Retractorless brain surgery: technical considerations

Abstract: Background Retraction is necessary to access deep areas in the brain and skull base, but prolonged and forceful use of fixed retraction might be injurious. Several techniques were developed, in the concept of minimally invasive neurosurgery, to eliminate or minimize the use of fixed retractors. The authors discuss the technical considerations and limits in applying dynamic retraction in brain surgery for a variety of lesions using different approaches. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
(48 reference statements)
0
5
0
Order By: Relevance
“…Iatrogenic brain retraction injuries occur in around 10% of major procedures of cranial tumors and 5% of intracerebral aneurysms as previously reported (11)(12)(13)(14)(15). These injuries may range from mild edema to severe edema even contributing to mortality.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Iatrogenic brain retraction injuries occur in around 10% of major procedures of cranial tumors and 5% of intracerebral aneurysms as previously reported (11)(12)(13)(14)(15). These injuries may range from mild edema to severe edema even contributing to mortality.…”
Section: Discussionmentioning
confidence: 81%
“…In some difficult surgical lesions there is a need of rigid retractors i.e. 5.7% in the study reported by Nazim et al (15). Rigid fixed retractors hide the normal anatomy, moreover in longer procedures like resection of brain tumors or clipping an aneurysm, prolonged application of rigid fixed brain retractors can cause contusion, ischemia or edema to the surrounding brain tissue that may result in irreversible brain damage.…”
Section: Discussionmentioning
confidence: 99%
“…To provide some historical context to the surgical management of CSF leaks, the first instance of an intracranial repair of a CSF leak was in 1926, when a bifrontal craniotomy was performed and a fascia lata graft was sutured to repair the dural defect. This technique had a high risk of failure of up to 27% and required brain retraction, which had the possibility of causing injury to sensitive neurovascular structures [ 15 ]. To avoid brain retraction and its complications, a naso-orbital extracranial approach to repair leaks was pioneered in 1948 [ 16 ].…”
Section: History Of Anterior Skull Base and Cerebrospinal Fluid Leak ...mentioning
confidence: 99%
“…Some of the methods developed include dynamic retraction that involves surgeons periodically removing or reducing the retraction force applied to the tissue to allow blood perfusion. Positioning is a method that involves careful selection of the surgical route with tactful positioning of the patient to reduce or eliminate the need for retraction of healthy brain tissue 6,7 . Chemical methods of brain retraction use pharmaceuticals to reduce intercranial pressure and volume to give greater access 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Adding to the difficulties, recent studies into retraction injuries are often missing key information such as retraction time or pressure 9 . Positioning may be useful in certain situations, but there are still cases where positioning cannot eliminate the need for retraction 7,10 . Additionally, positioning can cause other injuries to the patient due to the required position and duration 2 .…”
Section: Introductionmentioning
confidence: 99%